1995
DOI: 10.1029/95jd00512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land cover type and greenness on advanced very high resolution radiometer bidirectional reflectances: Analysis and removal

Abstract: The objectives of the study are (1) to examine the effects of land cover type, green biomass, and solar zenith angle (SZA) on the bidirectional reflectance distributions (BRDs) of the visible and near‐infrared advanced very high resolution radiometer (AVHRR) data from NOAA 11 over terrestrial surfaces; and (2) to correct for these effects by developing BRD functions (BRDF). Four land cover types are examined: barren, grassland, forest, and cropland. The data used consist of 1‐km daily AVHRR measurements for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(55 citation statements)
references
References 45 publications
0
55
0
Order By: Relevance
“…Therefore it is important to note, that given the varying viewing angles the BRDF might have an effect on the classification accuracy results presented in this study, as for instance showed by Sue et al (2009) [69], Vanonckelen et al (2013) [70] and Wu and Cihlar (1995) [71].…”
Section: Discussionmentioning
confidence: 95%
“…Therefore it is important to note, that given the varying viewing angles the BRDF might have an effect on the classification accuracy results presented in this study, as for instance showed by Sue et al (2009) [69], Vanonckelen et al (2013) [70] and Wu and Cihlar (1995) [71].…”
Section: Discussionmentioning
confidence: 95%
“…The narrow-to-broadband conversion algorithms have reported uncertainties of 5-10 % (Liang, 2000;Xiong et al, 2002). The BRDF correction and spectral albedo calculation for vegetation (Roujean et al, 1992;Wu et al, 1995) is estimated to have an uncertainty in the same order of magnitude. Cloud mask misclassifications cause the largest retrieval errors, but they occur only sporadically so that their effect on the temporal means is generally low.…”
Section: Atmosmentioning
confidence: 92%
“…Next, anisotropic reflectance (over vegetated/barren surfaces) is corrected and the surface reflectances are converted into spectral albedo after Wu et al (1995) and Roujean et al (1992). Broadband albedo is retrieved according to land cover type.…”
Section: The Clara-sal Retrieval Algorithmmentioning
confidence: 99%
See 2 more Smart Citations